Impact of E2 and FSH levels on the severity of Stress Urinary Incontinence (SUI) in menopausal women - Leny Suardi; Pribakti Budinurdjaja; Wiwit Agung Sri Nurcahyawati; Meitria Syahadatina Noor (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. E2 and FSH levels in menopausal women are thought to have relationship with stress urinary incontinensia (SUI).2. It was found that E2 and FSH levels had no significant relationship with SUI severity in menopausal women.   ABSTRACT Objectives: This study aimed to analyze the relationship between E2 and FSH levels in menopausal women with the severity of Stress Urinary Incontinence (SUI) at Ulin Hospital, Banjarmasin, Indonesia. Materials and Methods: This study used an analytic observational method with cross-sectional design in menopausal women diagnosed with Urinary Incontinence (UI) from October 2020 - March 2021. The independent variables were E2 and FSH levels. The dependent variable was the severity of SUI in menopausal women. The severity of SUI was determined by the Incontinence Severity Index (ISI) scoring. Data were analyzed by Spearman correlation. Results: The subjects who met the criteria were 25 women. The results showed the prevalence rate of SUI was 5.8% with E2 and FSH levels of mild SUI (14.25 pg/mL and 49.70 mIU/mL), moderate (7.91 pg/mL and 54.13 mIU/mL), and severe (9.14 pg/mL) and 70.97 mIU/mL). The number of severity levels of mild SUI was 44%, moderate SUI was 48%, and severe SUI was 8%. Most patients with SUI aged >60 years, multipara, normal body mass index (BMI), duration of menopause <10 years, menarche <15 years, Intrauterine Device (IUD) contraception, and delivered with spontaneous vaginal delivery. There was no significant relationship between E2 levels and the severity of SUI with a p-value of 0.084 and a correlation coefficient of -0.353. There was no significant relationship between FSH level and severity of SUI with a p-value of 0.367 and a correlation coefficient of 0.189. Conclusion: There was no significant relationship between E2 and FSH levels and the severity of SUI in menopausal women. It is necessary to do research on other factors that influence the high severity of SUI in menopausal women.